Time, space and technology in radiotherapy departments: how do these factors impact on patients' experiences of radiotherapy? - Merchant, Susan; O'Connor, Moira; Halkett, Georgia (Wiley-Blackwell Publishing Ltd., 2017)
Radiation therapists (RTs) plan and deliver radiotherapy treatment for patients diagnosed with cancer. They need to communicate regularly with their patients and may have a role to play in reducing patient anxiety and distress. The objectives were to explore how the environment of radiotherapy departments supports or inhibits communication generally and information giving and supportive care provision in particular. An ethnographic approach was used to gather rich descriptive data through observations and interviews conducted in two Australian radiotherapy centres. Time, space and a technology driven culture was found to negatively affect the quality of interaction that occurred between RTs and their patients. This research has shown design/modification of spaces is needed in the radiotherapy environment to reflect a patient care centred culture and to enhance opportunities for RTs to provide supportive care for their patients.